Efficacy and safety of lixisenatide once daily versus placebo in type 2 diabetes insufficiently controlled on pioglitazone (GetGoal‐P). Issue 11 (26th May 2013) - Pinget, M.; Goldenberg, R.; Niemoeller, E.; Muehlen‐Bartmer, I.; Guo, H.; Aronson, R.
<x xml:space="preserve">Abstract</x> Aims To compare the efficacy and safety of once‐daily prandial lixisenatide with placebo in type 2 diabetes mellitus (T2DM) insufficiently controlled by pioglitazone ± metformin. Methods This randomized, double‐blind study included a 24‐week main treatment period and a ≥52‐week variable extension period. Patients were randomized 2 : 1 to receive lixisenatide 20 µg once daily or placebo. The primary endpoint was change in glycated haemoglobin (HbA1c) at week 24. Results In total, 484 patients were randomized: 323 to lixisenatide; 161 to placebo. After 24 weeks, lixisenatide once daily significantly improved HbA1c (−0.56% vs. placebo; p < 0.0001) and increased the proportion of patients achieving HbA1c <7% compared with placebo (52.3% vs. 26.4%, respectively; p < 0.0001) and significantly improved fasting plasma glucose (−0.84 mmol/l vs. placebo; p < 0.0001). There was a small decrease in body weight with lixisenatide once daily and a small increase with placebo, with no statistically significant difference between the two groups. Overall, lixisenatide once daily was well tolerated, with a similar proportion of treatment‐emergent adverse events (TEAEs) and serious TEAEs between groups (lixisenatide: 72.4% and 2.5%; placebo: 72.7% and 1.9%). Symptomatic hypoglycaemia rates were also relatively low in both groups (lixisenatide 3.4% and placebo 1.2%), with no severe episodes. Lixisenatide continued to be efficacious and well tolerated during the variable extension period. Conclusions Lixisenatide once daily significantly improved glycaemic control with a low risk of hypoglycaemia, and was well tolerated over 24 weeks and during the long‐term, double‐blind extension period in patients with T2DM insufficiently controlled on pioglitazone ± metformin.